Flame spray coating of α-tricalcium phosphate on AISI 316L alloy. Issue 1 (31st December 2022) - Taqriban, R. B.; Fitriyana, D. F.; Ismail, R.; Jamari, J.; Bayuseno, A. P.
Abstract: The use of hydroxyapatite derived from green mussel (Perna Viridis) shell wastes for implant coating was investigated in this study. The study looked into using a flame-spraying technique to deposit this low-cost hydroxyapatite on AISI 316 L alloy. A standardized pull-off test on a coating thickness of 56–70 µm and a porous layer yielded a coating strength of 4.12 MPa. A melted hydroxyapatite layer with uniformly dispersed particles was visible in the SEM micrograph. The chemical elements C, Ca, Fe, Ni, P, and O corresponding to calcium orthophosphate and the alloy were revealed by EDX analysis of the coating layer. The α-tricalcium phosphate (α-TCP) found on the coating was confirmed by XRD Rietveld analysis. When the alloy is used as an implant, this α-TCP layer coating appears to have the potential to improve biocompatibility